Role of NDE1 in the Development and Evolution of the Gyrified Cortex - Soto-Perez, Jaseph; Baumgartner, Marybeth; Kanadia, Rahul N. (Frontiers in Neuroscience, 2020)
An expanded cortex is a hallmark of human neurodevelopment and endows increased cognitive capabilities. Recent work has shown that the cell cycle-related gene NDE1 is essential for proper cortical development. Patients who have mutations in NDE1 exhibit congenital microcephaly as a primary phenotype. At the cellular level, NDE1 is essential for interkinetic nuclear migration and mitosis of radial glial cells, which translates to an indispensable role in neurodevelopment. The nuclear migration function of NDE1 is well conserved across Opisthokonta. In mammals, multiple isoforms containing alternate terminal exons, which influence the functionality of NDE1, have been reported. It has been noted that the pattern of terminal exon usage mirrors patterns of cortical complexity in mammals. In order to provide context to these findings, here we provide a comprehensive review of the literature regarding NDE1, its molecular biology and physiological relevance at the cellular and organismal level. In particular, we outline the potential roles of NDE1 in progenitor cell behavior and explore the spectrum of NDE1 pathogenic variants. Moreover, we assessed the evolutionary conservation of NDE1 and interrogated whether the usage of alternative terminal exons is characteristic of species with gyrencephalic cortices. We found that gyrencephalic species are more likely to express transcripts that employ the human-associated terminal exon, whereas lissencephalic species tend to express transcripts that employ the mouse associated terminal exon. Amongst gyrencephalic species, the human-associated terminal exon was shown to be preferentially expressed by those with a high order of gyrification. These findings underscore phylogenetic relationships between the preferential usage of NDE1 terminal exon and high order gyrification, which provide insight into cortical evolution underlying high order brain functions.